Isolated Abdominal Wall Metastasis of Endometrial Carcinoma - Rita Luz; Rui Leal; Jorge Simões; Matilde Gonçalves; Isabel Matos (Case Reports in Obstetrics and Gynecology)
A woman in her mid-60s presented with a bulky mass on the anterior abdominal wall. She had a previous incidental diagnosis of endometrial adenocarcinoma FIGO stage IB following a vaginal hysterectomy. Physical exam and imaging revealed a well circumscribed bulging tumour at the umbilical region, measuring 10 × 9 × 9 cm, with overlying intact skin and subcutaneous tissue. Surgical resection was undertaken, and histological examination showed features of endometrial carcinoma. She began chemotherapy and is alive with no signs of recurrent disease one year after surgery. This case brings up to light an atypical location of a solitary metastasis of endometrial carcinoma.